MENINGKATKAN KEMAMPUAN MEMBACA MELALUI METODE BERMAIN FLASHCARD PADA SISWA KELAS 2 MI AL-HIDAYAH BANJARSARI - Nugraheni, Dita Amalia; Amelasasih, Prianggi (Universitas Tanjungpura, 2024)
This study investigates the effectiveness of the flashcard method in enhancing reading skills among second-grade students at MI AlHidayah Banjarsari. Using a qualitative descriptive approach, the research focuses on a single subject, AZM, who demonstrated limited reading ability. Data collection was conducted through interviews, observations, and assessments, and the intervention was divided into three stages: pre-test, intervention, and post-test. Structured reading activities using flashcards were implemented during these stages. The findings revealed significant improvements in AZM's reading proficiency, vocabulary development, and confidence. Initially, the subject struggled with basic word recognition and pronunciation. However, the interactive and visually engaging nature of flashcards facilitated notable progress. By the end of the intervention, the subject displayed marked advancements in word recognition and sentence construction, alongside increased enthusiasm and focus during learning sessions. The study concludes that flashcards are an effective educational tool, particularly for early learners, as they combine visual stimulation with interactive learning. It recommends the integration of flashcards into classroom activities by educators and active parental involvement at home to reinforce reading development. This method offers a practical and engaging approach to addressing early reading challenges in young learners.